At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

a student is trying to solve the system of two equations given below:equation P: y + z = 6equation Q: 5y + 9z = 1Which of the following is a possible step used in eliminating the y-term?A: (y + z = 6) × 9B: (y + z = 6) × -5C: (5y + 9z = 1) × 9D: (5y + 9z = 1) × 5

Sagot :

we have the system

y + z = 6 ------> equation P

5y + 9z = 1 -----> equation Q

i will solve by elimination

step 1

Multiply the equation P by -5

so

(y + z = 6) *-5

-5y-5z=-30

adds equation Q

-5y-5z=-30

5y + 9z = 1

------------------

5z+9z=-30+1

therefore

the answer is the option B

Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.